Case Study: Control of respiratory disease in male Holstein calves with tildipirosin and effect on health and growth from 0 to 4 months of age - Hill, T.M. (Prof Anim Sci, 2018)
In trial 1, phase 1, 48 male Holstein calves initially 2 to 4 d of age were transported 3.5 h to the research facility. Calves were randomly selected to either receive a s.c. injection of Zuprevo (Merck Animal Health, Summit, NJ; 4 mg of tildipirosin/kg of BW; TIL) the day after arrival (d 0) and again at weaning (d 42) or receive no injections (CON). Calves were fed 0.66 kg of milk replacer DM daily for 39 d and then 0.33 kg daily for 3 d. A starter was fed free choice for the 56 d of phase 1. In trial 1, phase 2, the same calves from phase 1 grouped by CON and TIL were moved to group pens (4 pens per treatment, 4 calves per pen) for the next 56 d. The starter was blended with 5% chopped grass hay and fed free choice. Trial 2 was similar to trial 1, phase 2 and used 48 two-month-old male Holstein calves. Calves were randomly selected to receive either a s.c. injection of Zuprevo (4 mg of tildipirosin/kg of BW; TIL) on d 0 or no injections (CON). In trial 1, phase 1, preweaning ADG and BCS change; postweaning starter intake and hip width change; overall starter intake, ADG, and hip width change; final hip width; and final BCS were greater for TIL than CON. During phase 2 of trial 1 and trial 2, calf ADG and hip width change were greater for TIL than CON. Overall, in transported Holstein calves, TIL improved ADG and structural growth by approximately 13%.